PENGARUH VARIASI LAPISAN (1-3) ANYAMAN SERAT TERHADAP KEKUATAN TARIK DAN IMPAK KOMPOSIT RESIN BERPENGUAT SERAT RESAM - syahrian, arbi; Juanda, Juanda; Zulfitriyanto, Zulfitriyanto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Resam (Dicranopteris linearis syn. Gleichenia linearis) can be used as an alternative raw material. This material is easy to obtain because it can be used in almost all corners of Indonesia, especially the Bangka Belitung area, is easy to process, and has a size of stem content and stem size. Has good mechanical properties, corrosion resistance, easy to obtain from nature and environmentally friendly raw materials. So it can be developed as a composite material. This study aims to determine the effect of variations in layers (1-3) of woven fibers on the tensile strength and impact of resin-reinforced composites. In this study, using variations in the number of different layers, namely 1 layer, 2 layer, and 3 layer. The material used is resam woven fiber resin. Tensile test specimens were made with reference to the ASTM D-638 standard and impact testing according to ISO-179. The research results show,. The highest tensile strength value is found in the 1-layer layer, which is 26.4 MPa and the highest impact strength is owned by the 3-layer composite, which is 0.09014 J/mm2. Based on the results of the comparison test, the number of fiber layers greatly affects the tensile and impact strength.